Experimental study on cyclic loading characteristics of fly ash as partial replacement of cement in beam-column joint. (December 2020) - Shaw, Sayan Kumar; Sil, Arjun
Highlights: Fly ash is being used as a replacement material of cement applying in BCJ to examine the seismic performance. Five types of exterior BCJs investigated experimentally for a curing of 28 days. There is 11 % higher ductility as well as 7 % higher dissipation energy observed for 20FAS28 sample. Brittleness index (BI) is alike for 20FAS28 sample with control concrete joint. Abstract: Fly ash (FA) is a byproduct obtained after burning of coal in power plant as waste, however considered as one of the building materials having reasonable binding properties. Indeed, in this study, FA is being used as a surrogate material of cement essentially to study the cyclic loading characteristics applying in a beam-column joint (BCJ) to examine the seismic performance during high magnitude earthquake (Mw>6) having larger duration sustaining of corner frequency of an event responsible for damages. Nevertheless, in a BCJ, beam is primarily designed considering under-reinforced condition or allowed the section to fail through plastic hinge formation (i.e. ductility) so that dissipation of energy could be controlled by forming capacity of column-beam ratio 1.4 as per IS-1893-2016 and IS-456. Conversely, in this study, five types of exterior BCJs prepared and investigated experimentally for a curing of 28 days. Further, flexural strength ratio of the sample maintained as 2.0. It has been observed that, 20FAS28 sample provides as well as performed well in the higher displacement level than control concrete. Indeed, stiffness degradation exhibits slightly higher than the control concrete. On the other hand, there is 11 % higher ductility as well as 7 % higher dissipation energy observed for 20FAS28 sample than other samples. Further, it has been found that brittleness index (BI) is similar for 20FAS28 sample with control concrete. This study explores identifying the suitability of FA ranges and helps to understand the effects of admixtures for it's effective utilization in the field application as an alternative material and thereby expecting minimizing the construction cost.